Digital Hadith and Gendered Harm: Negotiating Religious Authority and Female Circumcision Discourses on Instagram - Wahyu Elvita Rohmi; Mukhammad Zamzami; Wael Hegazy (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
The digital reproduction of weakly authenticated hadiths used to support the practice of female genital mutilation (FGM/C) exacerbates health risks. It reinforces patriarchal bias within Muslim communities, thereby eroding gender justice and maqāṣid al-sharī‘ah amidst the democratization of religious authority on social media. Although the World Health Organization (WHO) has designated FGM/C as a harmful practice with serious medical and psychological consequences, some Indonesian Muslim groups continue to perpetuate it through cultural and religious legitimacy, creating tensions between textual tradition, human rights principles, and the dynamics of online discourse. This study addresses this gap by analyzing hadith narratives on the Instagram account @halalcorner, integrating hadith criticism and digital netnography to explore the negotiation of religious authority. Using a qualitative-descriptive netnography approach, data were collected through non-participant observation (March–August 2025) of 12 core posts, 1,256 user comments, and multimodal elements, with purposive sampling based on keywords and engagement levels. The analysis followed Kozinets’ four-stage model (investigation, immersion, interaction, integration), with validity maintained through methodological, researcher, and theoretical triangulation, as well as Cohen’s kappa calculation (yielding 85% agreement), peer debriefing, and an audit trail. The findings reveal a dominance of pro-circumcision narratives (70%), followed by opposition narratives (15%) and neutral narratives (15%). The cited hadith tend to emphasize the notion of ​​ṭahārah rather than legal prescriptions, revealing interpretive biases that contradict the protection of life and lineage. By drawing on feminist theology and digital religion theory, this study underscores the need for online discourse that is more reflective, humanistic, and aligned with Islam’s vision as a mercy for all creation.